EFEKTIVITAS PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISTEM PERSAMAAN LINEAR TIGA VARIABEL SISWA KELAS X SMK YAPIS TIMIKA - A. Rasul; Subhanudin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Abstract: This study aims to determine whether the CTL model is effective on the learning outcomes of Class X students of SMK Yapis Timika. The type used in this research is experimental research. This research was conducted at Yapis Timika Vocational School, Mimika Regency as a place for the implementation of the CTL model and the class used was class X Accounting with a total of 13 people. Research results and application. (1) based on the results of the normality test using statistical software on the pretest value and posttest value with a level of = 5% is a normal distribution where the pretest value is 0.200 < 0.234 and 0.040 < 0.234 (2) based on the effectiveness test using the One-Sample T-test, the application of the CTL model is effective on learning outcomes of the Three-variable Linear Equation System for Class X students of SMK Yapis Timika, where the value of Sig.(2-tailed) = 424 0.05. Thus the CTL model is effective on the learning outcomes of SPLTV students of SMK Yapis Timika class X Accounting, mathematics teachers should use the CTL model as an alternative in the learning process.